2012
DOI: 10.1097/ico.0b013e31821e4286
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Corneal Thickness Measurements During Corneal Collagen Cross-Linking With Hypoosmolar Riboflavin Solution in Thin Corneas

Abstract: The iatrogenic swelling effect of the hypoosmolar riboflavin solution might be short acting and not durable throughout the UVA application in collagen cross-linking procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 26 publications
4
41
0
5
Order By: Relevance
“…These data correlate well with our data regarding the decrease in thickness. Kaya et al (38) measured corneal thickness at 5 different times: the thinnest pachymetry data decreased to a mean of 376 µm after the epithelial removal and by a mean of 55 µm after the 30-minute application of the isotonic riboflavin solution. The 10-minute application of hypotonic riboflavin resulted in the cornea thickening by a mean of 59 µm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data correlate well with our data regarding the decrease in thickness. Kaya et al (38) measured corneal thickness at 5 different times: the thinnest pachymetry data decreased to a mean of 376 µm after the epithelial removal and by a mean of 55 µm after the 30-minute application of the isotonic riboflavin solution. The 10-minute application of hypotonic riboflavin resulted in the cornea thickening by a mean of 59 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hypoosmolar riboflavin solution is suggested in order to achieve corneal iatrogenic swelling (37), although according to previous research it has only a short-term effect and does not even last until the end of the treatment (38). Publications found in the literature clearly describe the CCT decrease observed after CXL treatment, though only a few and contradicting reports were carried out on the characteristics of CCT decrease in the intraoperative phase (35,38,39). Using isotonic solution, Kymionis et al (35) detected a mean 75 µm CCT decrease between epithelial removal and riboflavin instillation with ultrasound pachymetry measurements; however, they found no further changes in corneal thickness during irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In their studies, a lid speculum was kept in the eye during the whole procedure. Another research (16) showed a twostep TCT decrease of 19% during the 60-minute treatment: a slower thinning during riboflavin instillation (without a lid speculum) and a faster thinning when a lid speculum hold the lids open during UVA exposure. In all these studies, corneal exposure may have contributed to a higher corneal thickness decrease during the procedure and in the early postoperative CXL course.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (15,16) found significant TCT decrease of about 17 to 20% in central corneal thickness 30 minutes after iso-osmolar riboflavin drops. In their studies, a lid speculum was kept in the eye during the whole procedure.…”
Section: Discussionmentioning
confidence: 99%
“…При этом использование изоосмолярного рибофлавина с декстраном способно привести к снижению толщины человеческой роговицы в среднем на 55 мкм продолжительностью около 30 мин. Однако все-таки возможен кросслинкинг при корне-альной толщине 250−350 мкм за счет искусственного предоперационного отека роговицы, увеличивающего ее толщину до 60 мкм, гипоосмолярным раствором ри-бофлавина [67]. Предложена также оригинальная ме-тодика кросслинкинга тонких роговиц (350−400 мкм) с использованием контактных линз, пропускающих УФ-излучение [68].…”
Section: уф-кросслинкинг тонких роговицunclassified